Invasion of Eukaryotic Cells by Legionella Pneumophila: A Common Strategy for all Hosts? - Paul S Hoffman (Canadian Journal of Infectious Diseases)
Legionella pneumophila is an environmental micro-organism capable of producing an acute lobar pneumonia, commonly referred to as Legionnaires’ disease, in susceptible humans. Legionellae are ubiquitous in aquatic environments, where they survive in biofilms or intracellularly in various protozoans. Susceptible humans become infected by breathing aerosols laden with the bacteria. The target cell for human infection is the alveolar macrophage, in which the bacteria abrogate phagolysosomal fusion. The remarkable ability of L pneumophila to infect a wide range of eukaryotic cells suggests a common strategy that exploits very fundamental cellular processes. The bacteria enter host cells via coiling phagocytosis and quickly subvert organelle trafficking events, leading to formation of a replicative phagosome in which the bacteria multiply. Vegetative growth continues for 8 to 10 h, after which the bacteria develop into a short, highly motile form called the ‘mature form’. The mature form exhibits a thickening of the cell wall, stains red with the Gimenez stain, and is between 10 and 100 times more infectious than agar-grown bacteria. Following host cell lysis, the released bacteria infect other host cells, in which the mature form differentiates into a Gimenez-negative vegetative form, and the cycle begins anew. Virulence of L pneumophila is considered to be multifactorial, and there is growing evidence for both stage specific and sequential gene expression. Thus, L pneumophila may be a good model system for dissecting events associated with the host-parasite interactions.